2016
DOI: 10.1128/mcb.00292-16
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 1 Is a Substrate for p38 Mitogen-Activated Protein Kinases

Abstract: Heat shock factor 1 (HSF1) monitors the structural integrity of the proteome. Phosphorylation at S326 is a hallmark for HSF1 activation, but the identity of the kinase(s) phosphorylating this site has remained elusive. We show here that the dietary agent phenethyl isothiocyanate (PEITC) inhibits heat shock protein 90 (Hsp90), the main negative regulator of HSF1; activates p38 mitogen-activated protein kinase (MAPK); and increases S326 phosphorylation, trimerization, and nuclear translocation of HSF1, and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 64 publications
3
67
0
Order By: Relevance
“…The phosphorylation of serine 326 of HSF1 allows DAXX to bind to HSF1 to enhance its transcription , and mutations of serine 326 have been reported to reduce the transcriptional activity of HSF1 . Several kinases have been implicated in phosphorylating HSF1 at serine 326, including the mechanistic target of rapamycin , the MAPK kinase MEK and the p38 MAPK . Notably, among the p38 MAPK family members, p38δ MAPK is a particularly efficient catalyst of this phosphorylation, whereas p38γ MAPK is the most specific .…”
Section: Post‐translational Modifications Of the Hsf1 Proteinmentioning
confidence: 99%
“…The phosphorylation of serine 326 of HSF1 allows DAXX to bind to HSF1 to enhance its transcription , and mutations of serine 326 have been reported to reduce the transcriptional activity of HSF1 . Several kinases have been implicated in phosphorylating HSF1 at serine 326, including the mechanistic target of rapamycin , the MAPK kinase MEK and the p38 MAPK . Notably, among the p38 MAPK family members, p38δ MAPK is a particularly efficient catalyst of this phosphorylation, whereas p38γ MAPK is the most specific .…”
Section: Post‐translational Modifications Of the Hsf1 Proteinmentioning
confidence: 99%
“…As presented in Figure 3F, exposure of MEFs to 40°C for 5 minutes was sufficient for Hsf1 303A/307A protein appearance in the nuclear fraction while significantly higher stress was required for WT. Hsf1 phosphorylation of serine residue at S326 has been shown to represent activated Hsf1 (26,27). We also investigated the Hsf1 pS326 phosphorylation status when cells were incubated at 37°C, 40°C or 42°C for 30 minutes using WT or Hsf1 303A/307A MEFs.…”
Section: Phosphorylation Of Hsf1 At S303/s307 Indicates Repression Ofmentioning
confidence: 99%
“…Within minutes, PEITC induced the phosphorylation of HSF1 at S326 as well as the activation of the p38 mitogen‐activating protein kinases (MAPKs) 56. By the use of p38 MAPK inhibitors, we found that the p38 gamma isoform was, in part, responsible for the phosphorylation of HSF1 pS326 upon PEITC exposure.…”
Section: Peitc Activates the Hsf1‐dependent Heat Shock Responsementioning
confidence: 94%
“…In cervical cancer HeLa cells stably transfected with the HSP70.1 promoter fused upstream of the luciferase gene, PEITC robustly induced the promoter activity in a time‐ and dose‐dependent manner 56. HSP70, the prototypic marker of activation of the HSF1‐mediated transcription, was induced by PEITC and the induction was absent in MEF cells deficient in HSF1, suggesting that PEITC induced the HSR by activating HSF1 56. In agreement with our findings, PEITC treatment in murine hepatoma Hepa1c1c7 cells induced the HSP70 gene expression 47a.…”
Section: Peitc Activates the Hsf1‐dependent Heat Shock Responsementioning
confidence: 99%
See 1 more Smart Citation